Pelatihan dan Pendampingan Kader tentang Self Monitoring of Blood Glucose (SMBG) dalam Upaya Deteksi Dini dan Menciptakan Warga Bebas DM - Sucipto, Adi Sucipto; Desty Ervira Puspaningtyas; Cornelia D.Y Nekada; Puspita Mardika Sari (Jurnal Pengabdian Pada Masyarakat, 2022)
Diabetes mellitus (DM) is a health problem globally and in Indonesia. One of the pillars of diabetes management is health education. One of the health education materials that can be given is how to measure blood sugar levels independently, known as Self onitoring of Blood Glucose (SMBG). This training and assistance are intended primarily for health cadres, DM patients, or those at risk of developing DM. The service team’s assessment results showed that health cadres, patients, and families of DM patients in Padukuhan Gondang Legi, Wedomartani Village, had never received health education about SMBG training. Therefore, the health education material provided is training and assistance in measuring blood sugar levels independently or Self Monitoring of Blood Glucose (SMBG). The purpose of this service is to improve the knowledge and skills of cadres, DM patients, and residents in measuring blood sugar levels independently so that residents can carry out early detection (screening) or monitor their blood sugar levels independently. The service is carried out in 3 stages in September – November 2021 in Padukuhan Gondang Legi, Wedomartani Village, Ngemplak, Sleman. The service is conducted in education using the focus group discussion (FGD) method and direct demonstration of blood sugar levels to cadres, DM patients, and families. The provision of education and training increases the understanding of cadres and residents about SMBG. The change in the average knowledge score from 38.3 before education to 88.7 after education with an average difference of 50.4 Assistance and education to cadres and residents need to be carried out intensively and continuously to increase knowledge, which will impact changing attitudes and behavior of residents in efforts to control and prevent DM.